MYLORRY: An Android Based Mobile Application for Lorry Transport Services - Krishnan, Shivashakthi; Suhaimi Abd. Ishak (Applied Information Technology And Computer Science, 2021)
Transportation can be considered as a competitive major contributor for the economy in terms of business. In particular, lorry transport service industry is huge, diverse and very competitive industry worldwide as there are various type of lorries that will be needed based on the cargo which being transported. However, lorry transport companies have very few platforms to promote their lorry transport service. This project attempts to design and develop a mobile application for lorry transport services on Android. It is a systematic application used for online lorry transport service for Malaysians that needs to book lorries with affordable price to transport bulk cargos for business or personal reasons. In addition, it serves a Management Information System for lorry transport service companies. This project applies Object-Oriented System Development (OOSD) Methodology. An object-oriented software consist of a set of objects that interrelate with one another. The expected results from this project is a mobile application for lorry transport services. The application consists of three modules which are Admin module, Lorry Owner module and Customer module. This application benefits lorry companies in handling the online transport service management and helps customers to find suitable lorries services with affordable price.